Application of Fuzzy Logic in Making Automatic Labeling Stamping - Putra, Ondra Eka (Politeknik Ganesha Medan, 2019)
This research was conducted to create a labeling system on cardboard boxes with automatic stamping. Labeling is done based on height and weight of the cardboard so that stamping will be done according to the size and weight of the cardboard. The height of the cardboard is detected using an ultrasonic sensor and the weight of the cardboard is detected using a load cell sensor, and a stepper motor to move the cardboard label stamping. This research is based on artificial intelligence using mamdani method with fuzzy logic, so that all data can be processed properly. The height of the cardboard detected by the ultrasonic sensor is given a distance value of 10 cm to 45 cm with a value of rendah, sedang and tinggi. Cardboard weight detected by load cell sensor is given a weight value of 500 gr up to 1,500 gr with ringan, sedang and berat values. Stamping labels are driven by stepper motors which are given time values ​​of 5 s to 15 s with time values ​​of sebentar, sedang, and lama After the ultrasonic sensor and the load cell detect the cardboard box, the conveyor belt moves to run the cardboard box by the power window motor, then if the cardboard box passes through the proximity sensor, the conveyor belt stops and the stepper motor moves to stamping the cardboard label box automatically. The label stamping system is controlled by using the Arduino Mega 2560 to work well.